Settler women's experiences of fear, illness and isolation, with particular reference to the Eastern Cape Frontier, 1820-1890 - Dampier, Helen (Rhodes University, Faculty of Humanities, Department of History, 2000)
This thesis is an exploration of diaries and letters written by middle-class English-speaking settler women living on the Eastern Cape frontier between 1820 and 1890. By according primacy to these women's experiences and perceptions, it aims for a greater understanding of women's encounters with the frontier, and how these were articulated in their personal writing. An emphasis on the recurrent themes of ill-health, fearfulness and solitude undermines the popular myth of the brave, conquering, invincible pioneers which dominates settler historiography to date. The tensions felt by white women living on the frontier disrupted their identities as middle-class Victorian 'ladies', and as a result these women either constantly re-established a sense of self, or absorbed some aspects of the Eastern Cape, and thus redefined themselves. Settler women's experiences of the frontier changed little during the seventy year period spanned by this study, indicating that frontier life led to a rigidification and reinforcement of old, familiar values and behaviours. Rather than adapting to and embracing their new surroundings, settler women sought to duplicate accepted, conventional Victorian ideals and customs. White Victorian women identified themselves as refined, civilized, moral and respectable, and perceived Africa and Africans as untamed, immoral, uncivilized and threatening. To keep these menacing, destabilizing forces at bay, settler women attempted to recreate 'home' in the Eastern Cape; to domesticate the frontier by rendering it as familiar and predictable as possible. The fear, illness and solitariness that characterise settler women's personal writings manifest their attempts to eliminate alienating difference, and record their refusal to truly engage with the frontier landscape and its inhabitants.
Keywords: Women -- South Africa -- History; Women -- South Africa -- Eastern Cape -- Social conditions; Women -- South Africa -- Eastern Cape -- History; British settlers of 1820 (South Africa); Frontier and pioneer life -- South Africa